Models for biomass expansion factor of acacia hybrid (A. auriculiformis* A. mangium) plantations in the Southern region, Vietnam - Thi Ngoan, Tran; Tan Chung, Nguyen; Thi Ha, Nguyen; Thi Thuy Duong, Dao; Tuan Vu, Nguyen (Journal of Forestry Science and Technology, 2023)
Acacia hybrid is one of the favorably fast-growing species which is bring to potential benefits of agro-ecological and socio-economic sectors in Vietnam. The main objective of this study was to develop well-fitted models for estimating biomass expansion factor (BEF) for Acacia hybrid plantations. Fifty-four samples of Acacia hybrid trees from 2 to 10 years of age were collected from Acacia hybrid plantations in the Southern part of Vietnam. Total dry biomass including stems, branches and leaves were used to estimate an average value of BEF. The BEF value was calculated by taking the dry aboveground biomass (W) divided by the volume of merchantable tree woods over their barks (Vm). Twelve allometric equations were fitted by constructing regression models between BEF and inventory variables including diameter at breast height (DBH), height (H) and age (A). Consequently, the average value of BEF was 1.11 ton/m3. The BEF value had a strongly negative relationship with DBH, height and age in which the BEF value decreased as these three parameters increased. Two best fitted models for estimating a BEF value of Acacia hybrid (A. auriculiformis * A. mangium) plantations included: BEF = 1.99865 - 0.15400*DBH - 0.02123*H + 0.18210*A; and BEF = 3.01307 - 2.44459*ln(DBH) - 0.10171*DBH -2.06212*ln(H) + 1.54556*ln(DBH*H*A). Estimated values of above-ground biomass by utilizing the fitted BEF values from two these models were similar. Results of the study indicated that use of a fitted BEF model is fundamental to obtain reliable estimates of biomass and CO2 equivalent for Acacia hybrid plantations.